Pengaruh Kualitas Makanan Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Di Moka Restoran Pada Astagina Resort Villa And Spa, Legian Bali - Hanung, Yuliana Devila; Sutapa, I Ketut; Dewi, Desak Made Purnama (Universitas Triatma Mulya, 2023)
In businesses engaged in the service sector, customer satisfaction is the most important thing to maintain, which will certainly have a very good impact on the business going forward. This is the main background of the research entitled